Cartilage Substitutes: Graphene Oxide‐Doped Gellan Gum–PEGDA Bilayered Hydrogel Mimicking the Mechanical and Lubrication Properties of Articular Cartilage (Adv. Healthcare Mater. 7/2021). Issue 7 (7th April 2021) - Trucco, Diego; Vannozzi, Lorenzo; Teblum, Eti; Telkhozhayeva, Madina; Nessim, Gilbert Daniel; Affatato, Saverio; Al‐Haddad, Hind; Lisignoli, Gina; Ricotti, Leonardo
Abstract : In article number 2001434 by Leonardo Ricotti, Gina Lisignoli, Diego Trucco, and co‐workers, a bilayered hydrogel made of gellan gum and poly(ethylene glycol)diacrylate fills chondral defects of articular knee cartilage, mimicking the superficial and the deep zones in terms of mechanical and lubrication features. Graphene oxide dopant improves the superficial layer's lubrication. Such a nanocomposite hydrogel could be used as an injectable filler or a surgically implantable substitute in defects, showing no cytotoxicity, and guaranteeing suitable resistance to wear.